Extracellular Vesicles From the Cotton Pathogen Fusarium oxysporum f. sp. vasinfectum Induce a Phytotoxic Response in Plants - Bleackley, Mark R.; Samuel, Monisha; Garcia-Ceron, Donovan; McKenna, James A.; Lowe, Rohan G. T.; Pathan, Mohashin; Zhao, Kening; Ang, Ching-Seng; Mathivanan, Suresh; Anderson, Marilyn A. (Frontiers in Plant Science, 2020)
Extracellular vesicles (EVs) represent a system for the coordinated secretion of a variety of molecular cargo including proteins, lipids, nucleic acids and metabolites. They have an essential role in intercellular communication in multicellular organisms and have more recently been implicated in host-pathogen inteactions. Study of the role for EVs in fungal biology has focused on pathogenic yeasts that are major pathogens in humans. In this study we have expanded the investigation of fungal EVs to plant pathogens, specifically the major cotton pathogen Fusarium oxysporum f. sp. vasinfectum. EVs isolated from F. oxysporum f. sp. vasinfectum culture medium have a morphology and size distribution similar to EVs from yeasts such as Candida albicans and Cryptococcus neoformans. A unique feature of the EVs from F. oxysporum f. sp. vasinfectum is their purple colour which is predicted to arise from packaging of a napthoquinone pigment being packaged into the EVs. Proteomic analysis of F. oxysporum f. sp. vasinfectum EVs revealed that they are enriched in proteins that function in synthesis of polyketides as well as proteases and proteins that function in basic cellular processes. Infiltration of F. oxysporum f. sp. vasinfectum EVs into the leaves of cotton or N. benthamiana plants led to a phytotoxic response. These observations lead to the hypothesis that F. oxysporum f. sp. vasinfectum EVs are likely to play a crucial role in the infection process.